KONTEKSTUALISASI FILOSOFI PENDIDIKAN DALAM SISTEM PENDIDIKAN PERSEKOLAHAN :Studi Perbandingan Visi Sekolah Menengah Pertama SMP Sekolah Sukma Bangsa Di Bireuen Dan Sekolah Menegah Pertama Negeri SMPN I Bireuen - Zulkarnain, - (2011)
phisophical belief is crucial for the provision of educational services since it constitutes a basis for proper and successful educational processes. It is embedde in the formulation of educational vision, mission, and goals, and the formulation is frequently influenced by internal and external factors. Hence, the contextualization of educational philosphy in formal education system is frequently ignored. Consequently, education is not oriented to meet long term need, relevant to be objective of human life. On the ather hand, demand for high quality education is increasingly high. To meet the demand, technical concept, such as School Development Plan, School Activity Plant, and the like, are usually proposed without the consideration of educational philosophy. In general, ignoring the aspects of educational philosophy in schooling system will lead to poor quality of education. Based on the above mentioned issue, this study was conducted on two formal scooling institution in the District of Bireuen: Sukma Bangsa Junior High School and Junior High School I. The research question is how the school vision, mission and goals are, and hes the vision been implemented in educational processes?. Theoretical purpose of study is to construct a theory on the contextualization of educational philosophy in schooling system, and practical purpose of the study is to analyze the statement of vision, mission, and goals set by two schools. To discribe the research problem and achieve the research objectives, philosophical and scientific approaches heve been adopted to strengthen theoretical basis, and a hermeneutic method has been used to analyze verified data. Data collected from the research subject through interviews and documentary study have been descriptivly analyzed. The findings show that educational vision, mission and goals are set differenly, depending on who formulated them. Sukma Bangsa Junior High School hired expert to set them, whilw Junior High School I assigned schoole personnel to create them. Despitephilosophical values in the statement of vision, school personnel have not allegedly been aware of philosophical orentation to which educational processes refe